The integration of ict in initial teachers training: a proposal about learning and teaching evolution for future biology teachers of secondary school - Héctor Luis Gramaglia; Viviana Audisio (Ministerio de Educación, Dirección General de Educación Superior, 2018)
In order to make known educational approaches that integrate the construction of knowledges related to, not only the theory of evolution by an historical and epistemological perspective, but also perform as a teacher of actual secondary school like those ones relatives to the Information Communication Technologies (ICT), we present in this article a didactic sequence created and developed in the "History and Epistemology of Biology" seminary, corresponding to the third year of a biology secondary education teacher career in Córdoba Capital. The proposal, focused on the construction of knowledges about the synthetic theory of evolution worked in dialogue with the ICT tools involved by the work with a real case, associated with a legal conflict that included evolution analyses. The different activities proposed for learning, promoted the active participation of the students, and the generation of strengthened debates about the contents, and about the didactic and pedagogical potential of the performed work in general, and the integration of ICT tools in special.